Allometry and Ontogeny in the Vertebral Column of Southern Hemisphere Dolphins: a 3D Morphofunctional Approach - Marchesi, María Constanza; Mora, Matias Sebastian; Dans, Silvana Laura; González-José, Rolamdo (Journal of Mammalian Evolution)
Commerson’s dolphin (Cephalorhynchus commersonii), Peale’s dolphin (Lagenorhynchus australis), dusky dolphin (Lagenorhynchus obscurus), and hourglass dolphin (Lagenorhynchus cruciger) are closely related species occurring in the Southern Hemisphere. Even though they are partially sympatric, they have evolved towards diverse foraging strategies, prey, and habitat preferences. Size variation occurs both among and within species. Our goal was to study the allometric patterns and ontogenetic trajectories in the vertebral column of these dolphins related to their ecology. We choose nine functionally homologous vertebrae in each column and digitized five different tridimensional configurations, containing 28 to 41 landmarks depending on the functional region under analysis. We explored different levels of allometry (static, ontogenetic, and evolutionary) using multivariate regressions of shape vs. log-transformed centroid size. We compared ontogenetic allometry regression vectors to evidence differences in growth patterns. Finally, we calculated Procrustes distances of shape configurations to determine the timing of shape shifts. Of the studied species, When compared to the Lagenorhynchus species, Commerson’s dolphin showed the highest degrees of allometry, both static and ontogenetic. The macroevolutive trends indicate a high degree of evolutionary morphological change, which could be associated with the rapid evolutionary radiation proposed for the group. This is the first time that allometric changes are studied in small cetaceans by means of 3D geometric morphometrics. Fil: Marchesi, María Constanza. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Mora, Matias Sebastian. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. ...